Assent for children's participation in research: why it matters and making it meaningful. (2nd May 2016) - Oulton, K.; Gibson, F.; Sell, D.; Williams, A.; Pratt, L.; Wray, J.
Abstract: Background: There are gaps in the existing evidence base about assent, with conflicting and unhelpful views prevalent. We contend that appropriate assent is a valuable process that has important consequences for children's/young people's participation in research. Furthermore, there is a need for a model to support researchers in making decisions about who to assent and how to do this is a meaningful way. Methods: We undertook a scoping review of the literature to assess the body of opinion on assent in research with children/young people. An anonymous online survey was conducted to gather views from the wider community undertaking research with children/young people. We also sought to gather examples of current and effective practice that could be shared beyond the level of a single institution and our own experience. Survey participants included 48 health professionals with varied levels of experience, all actively involved in research with children. Results: Published work, the findings from the online survey and our knowledge as experienced researchers in the field have confirmed four domains that should be considered in order for assent to be meaningful and individualized: child‐related factors, family dynamics, study design and complexity and researcher and organizational factors. Mapping these domains onto the three paradigm cases for decision‐making around children and young people's assent/consent as recommended by the Nuffield Council on Bioethics has resulted in a model that will aid researchers in understanding the relationship between assent and consent and help them make decisions about when assent is appropriate. Conclusions: The debate about assent needs to move away from terminology, definition and legal issues. It should focus instead on practical ways of supporting researchers to work in partnership with children, thus ensuring a more informed, voluntary and more robust and longer lasting commitment to research.